NEW INEQUALITIES ON THE HOMOGENEOUS FUNCTIONS - V. Lokesha; K. M. Nagaraja; Y. Simsek (Journal of the Indonesian Mathematical Society, 2009)
"Pdf File"DOI : http://dx.doi.org/10.22342/jims.15.1.43.49-59